Paraffinoma of lips and oral mucosa: Case report and brief review of the literature - Friedrich, Reinhard E. (GMS Interdiscip Plast Reconstr Surg DGPW, 2014)
Interstitial application of paraffin in plastic and reconstructive surgery is obsolete due to the development of permanent and extensive foreign body granulomas at the site of application. These granulomas can cause severe physical impairment and develop their own prognostic worth. Furthermore, the disperse oil droplets are not a locally stable suspension. Therefore, the desired aesthetic aspect can get lost in the course of a potential dislocation of the suspension. In addition, the interstitial confluence of non-resorbable droplets to larger oil drops causes palpable and sometimes visible indurations of the skin, the correlate of chronic inflammation. This case report describes the efforts undertaken to release the patient at least temporarily from her paraffin granulomas and to improve her appearance. The relevant literature is briefly discussed. Furthermore, we present some immunohistochemical findings to specify the foreign body reaction associated with paraffin injections into connective tissues.